HUBUNGAN SANITASI ALAT MAKAN âPIRINGâ DENGAN ANGKA KUMAN PADA PERALATAN MAKAN PECEL LELE DI TAMBAKBAYAN BABARSARI SLEMAN - Sekarwati, Novita; Kristiani, Eva Runi (Jurnal Kesehatan Masyarakat, 2013)
ABSTRACTTo get qualified health foods , we need to hold control of hygiene and sanitation of food and eating utensils such as spoons , plates and cups , thisis for menghindarikan of pollution elements both physical , chemical andbacteriological.